Antiproliferative and proapoptotic effects of Inula viscosa extract on Burkitt lymphoma cell line. Issue 2 (February 2020) - Virdis, Patrizia; Migheli, Rossana; Galleri, Grazia; Fancello, Silvia; Cadoni, Maria Piera L; Pintore, Giorgio; Petretto, Giacomo Luigi; Marchesi, Irene; Fiorentino, Francesco Paolo; di Francesco, Alessandra; Sanges, Francesca; Bagella, Luigi; et al.
Burkitt lymphoma is a very aggressive B-cell non-Hodgkin lymphoma. Although remarkable progress has been made in the therapeutic scenario for patients with Burkitt lymphoma, search and development of new effective anticancer agents to improve patient outcome and minimize toxicity has become an urgent issue. In this study, the antitumoral activity of Inula viscosa, a traditional herb obtained from plants collected on the Asinara Island, Italy, was evaluated in order to explore potential antineoplastic effects of its metabolites on Burkitt lymphoma. Raji human cell line was treated with increasing Inula viscosa extract concentration for cytotoxicity screening and subsequent establishment of cell cycle arrest and apoptosis. Moreover, gene expression profiles were performed to identify molecular mechanisms involved in the anticancer activities of this medical plant. The Inula viscosa extract exhibited powerful antiproliferative and cytotoxic activities on Raji cell line, showing a dose- and time-dependent decrease in cell viability, obtained by cell cycle arrest in the G2/M phase and an increase in cell apoptosis. The treatment with Inula viscosa caused downregulation of genes involved in cell cycle and proliferation (c-MYC, CCND1) and inhibition of cell apoptosis (BCL2, BCL2L1, BCL11A). The Inula viscosa extract causes strong anticancer effects on Burkitt lymphoma cell line. The molecular mechanisms underlying such antineoplastic activity are based on targeting and downregulation of genes involved in cell cycle and apoptosis. Our data suggest that Inula viscosa natural metabolites should be further exploited as potential antineoplastic agents against Burkitt lymphoma.